2005
DOI: 10.1681/asn.2004050374
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of Cytokine Signaling Regulate Angiotensin II-Activated Janus Kinase-Signal Transducers and Activators of Transcription Pathway in Renal Cells

Abstract: Suppressors of cytokine signaling (SOCS) family is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 46 publications
5
44
0
1
Order By: Relevance
“…It has been well established that JAK/STAT pathway plays an important role in the proliferation of cells and in the production of TGF-b1 in diabetic nephropathy in vitro and in vivo, [24][25][26] we also confirmed this in our present investigation. However, we found that the increased phosphorylation of JAK2, STAT1 and STAT3 induced by HG was attenuated in all of the different combinations of probucol concentrations and exposure times.…”
Section: Discussionsupporting
confidence: 89%
“…It has been well established that JAK/STAT pathway plays an important role in the proliferation of cells and in the production of TGF-b1 in diabetic nephropathy in vitro and in vivo, [24][25][26] we also confirmed this in our present investigation. However, we found that the increased phosphorylation of JAK2, STAT1 and STAT3 induced by HG was attenuated in all of the different combinations of probucol concentrations and exposure times.…”
Section: Discussionsupporting
confidence: 89%
“…PEI-NPs are polymers that have been reported to effectively deliver oligonucleotides for modulating target gene expression in the kidney, as well as being considered preferable in preparing nonviral vectors because of their long-term safety and biocompatibility. 32,33,36,37 This study found that PEI-NPs were effective in delivering miR-146a to the kidneys, significantly increasing miR-146a expression. In addition, they did not increase the interferon response in obstructed kidneys.…”
Section: Discussionmentioning
confidence: 64%
“…31 Based on these findings, we hypothesized that miR-146a might strongly inhibit renal fibrosis by inhibiting the TGF-β 1 -Smad signaling pathway and inflammation in the kidney. To test this hypothesis, we used polyethylenimine (PEI) nanoparticles (NPs) (in vivo-jetPEI ® ), which have been reported effective in delivering oligonucleotides to the kidneys, 32,33 to deliver synthetic miR-146a to the kidneys in vivo. Using a mouse model of renal fibrosis induced by unilateral ureteral obstruction (UUO), we tested the effects of miR-146 overexpression on renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies Primary mouse mesangial cells (MC), vascular smooth muscle cells (VSMC) and a proximal tubuloepithelial cell line (MCT) were cultured in medium containing 10% FCS (Life Technologies, Rockville, MD, USA) [21][22][23][24]. Quiescent cells were treated for 90 min with peptides before short-term incubation with high glucose (HG; 30 mmol/l D-glucose, 60 min) or lipopolysaccharide (LPS; 1 μg/ml, 30 min; Sigma-Aldrich, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%